Development of parallel tests for numerical ability for student teacher in public university - Thiamtham, Thattharit (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this research is to develop three parallel tests and establish the norms for interpreting the scores from numerical ability test of teachers college students in public universities. The sample group in this study consisted of 1,993 fourth-yearteachers college students in public universities the academic year 2018. They were selected purposive sampling and multi-stage sampling. The results of the research show that the 3 parallel tests, each one consisting of 20 items, are of high quality in terms of content validity. Each item has IOC of 1.00. The difficulty level of the first, the second, and the third test were 0.68, 0.67, and 0.68, respectively. These three tests were parallel to one another. The score from each test was related to that of the other tests at statistical significance of 0.01. Correlation coefficient between Test 1 and Test 2, Test 1 and Test 3, and Test 2 and Test 3 were 0.96, 0.96 and 0.94 respectively. The means and the variances from the three tests did not differ. The norm was shown in a table presenting the relation between raw scores, percentile, stanine, and normal scores; the latter were ranging from 25-68.